Pengaruh Sistem Hidrogeologi Terhadap Gerakan Tanah Pada Ruas Jalan Buruma Dan Sekitarnya, Kecamatan Baucau Kabupaten Baucau, Propinsi Baucau Timor Leste - Antonio de Jesus, Armindo (ReTII, 2019)
The research area in Buruma Village and the surrounding area of Baucau sub-district, Baucau district of Timor Leste is a region that is very range of land movements. In the area there are two rock units, namely limestone Baucau formation and claystone of the Bobonaro Formation. The problem with this research is that the disasters of the land movement often result in material losses, land destruction, infrastructure and the impact on the regional growth rate is hampered. The purpose of this study is to determine the geological conditions of the study area, which include geomorphology, stratigraphy and geological structure, find out what type of soil movement is found in the study area, determine the effect of hydrogeological systems on soil movement and find out the appropriate handling methods for soil movement. The method used in this research is the study of literature as a preliminary guide, the method of soil sampling and laboratory testing using the method of SNI 1964. To find out the effect of the hydrogeological system on the ground motion, water flow measurements were taken in 9 studies, namely at the first location the amount of water debit was 0.198 m3 / s, the second location was 0.15 m3 / s, the third location was 0, 09 m3 / s, the fourth location is 0.086 m3 / s, the fifth location is 0.076 m3 / s, the sixth location is 0.071 m3 / s, the seventh location is 0.069m3 / s, the location eighth, the amount of water debit is 0.067 and the ninth location is the amount of water debit is 0.06 m3 / sec. The amount of water loss from Lp1-LP2 is 48 liters, Lp2-Lp3 is 60 liters, Lp3-Lp4 is 4 liters, Lp4-Lp5 is 18 liters, Lp5-Lp6 is 5 liters, Lp6-Lp7 is 2 liters, Lp7-Lp8 is equal to 18 liters 3 liters and Lp8-Lp9 of 7 liters. The way to overcome the occurrence of soil movement is to use the Geotextile method because the area is dominated by limestone, when exposed to water it dissolves easily and causes subsidence. In claystone water infiltrates into the soil / rock and adds to the burden on the road body and over time the movement of the soil.